The diagnostic challenge of psychiatric symptoms in neurodegenerative disease: rates of and risk factors for prior psychiatric diagnosis in patients with early neurodegenerative disease - Woolley, Josh D; Khan, Baber K; Murthy, Nikhil K; Miller, Bruce L; Rankin, Katherine P (The journal of clinical psychiatry, 2011)
To identify rates of and risk factors for psychiatric diagnosis preceding the diagnosis of neurodegenerative disease. Systematic, retrospective, blinded chart review was performed of 252 patients with a neurodegenerative disease diagnosis seen in our specialty clinic between 1999 and 2008. Neurodegenerative disease diagnoses included behavioral-variant frontotemporal dementia (n = 69), semantic dementia (n = 41), and progressive nonfluent aphasia (n = 17) (all meeting Neary research criteria); Alzheimer's disease (n = 65) (National Institute of Neurologic and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association research criteria); corticobasal degeneration (n = 25) (Boxer research criteria); progressive supranuclear palsy (n = 15) (Litvan research criteria); and amyotrophic lateral sclerosis (n = 20) (El Escorial research criteria). Reviewers remained blinded to each patient's final neurodegenerative disease diagnosis while reviewing charts. Extensive caregiver interviews were conducted to ensure accurate and reliable diagnostic histories. For each patient, we recorded history of psychiatric diagnosis, family psychiatric and neurologic history, age at symptom onset, and demographic information. A total of 28.2% of patients with a neurodegenerative disease received a prior psychiatric diagnosis. Depression was the most common psychiatric diagnosis in all groups. Behavioral-variant frontotemporal dementia patients received a prior psychiatric diagnosis significantly more often (50.7%; P < .001) than patients with Alzheimer's disease (23.1%), semantic dementia (24.4%), or progressive nonfluent aphasia (11.8%) and were more likely to receive diagnoses of bipolar disorder or schizophrenia than were patients with other neurodegenerative diseases (P < .001). Younger age (P < .001), higher education (P < .05), and a family history of psychiatric illness (P < .05) increased the rate of prior psychiatric diagnosis in patients with behavioral-variant frontotemporal dementia. Cognitive, behavioral, and emotional characteristics did not distinguish patients who did or did not receive a prior psychiatric diagnosis. Neurodegenerative disease is often misclassified as psychiatric disease, with behavioral-variant frontotemporal dementia patients at highest risk. While this study cannot rule out the possibility that psychiatric disease is an independent risk factor for neurodegenerative disease, when patients with neurodegenerative disease are initially classified with psychiatric disease, the patient may receive delayed, inappropriate treatment and be subject to increased distress. Physicians should consider referring mid- to late-life patients with new-onset neuropsychiatric symptoms for neurodegenerative disease evaluation.